032 Clinical frailty score as a decision-making tool in the emergency department – a step towards better outcomes for older patients. Issue 12 (21st November 2019) - Mitchell, Aine; Tahir, Qurrat-Ul-Ain; Banerjee, Jay
Abstract : Background: The ≥65 year age group don't always receive appropriate emergency care, occasionally due to ageism and as the 'medical' model of emergency care often does not benefit frail older patients. Over a six month period from December '18 - June '19, as part of a LeicGEM initiative, we aimed to: 1. Improve accurate calculation and documentation of the CFS for patients ≥65 years. 2. Increase utilisation of the CFS in providing individualised and holistic care for patients with frailty i.e. CFS ≥5. 3. Improve consideration of end-of-life care (EOLC) if CFS ≥7. Through monthly PDSA cycles, our frailty QI team introduced interventions including: info-posters disseminated through email, handover sessions, 'Champions' on the shop-floor, targeted educational sessions and leaflets. We utilised rapid-cycle audit information and staff perceptions survey to measure improvements and focus initiatives. In the last 6 weeks, we looked for sustainability of improvements. CFS documentation improved and remained accurate, which was sustained. Discussions with patients and families, and 'thought' given to offer holistic, individualised care both showed improvement, though this was not definitely sustained. EOLC discussions did not show any definite improvement. Frailty is a clinically important entity that is recognisable and accurately measurable by emergency physicians. If appropriately used, the CFS can help guide clinical care plans for patients. Simple interventions in a local ED setting were able to improve documentation and utilisation of the CFS to provide patient-centred care for older patients. Changing to a culture more open to EOLC discussions in the emergency setting was noted to be difficult both from our staff survey and audit data. This will need a more focused approach to improve departmental culture to have, and staff comfort to start an EOLC conversation. We will continue to advocate for use of CFS, and for better care for all our older patients.